Progression from youth to professional soccer: A longitudinal study of successful and unsuccessful academy graduates. (19th April 2021) - Dugdale, James H.; Sanders, Dajo; Myers, Tony; Williams, A. Mark; Hunter, Angus M.
Abstract : To optimize use of available resources, professional academies develop strategies to assess, monitor, and evaluate players as they progress through adolescence toward adulthood. However, few published reports exist using longitudinal study designs to examine performance throughout adolescence and the transition from youth to professional soccer. We examined differences in the age of player recruitment alongside longitudinal performance differences on field‐based fitness tests of successful vs. unsuccessful graduates across the entire age spectrum recruited by a professional soccer academy. Altogether, 537 youth soccer players volunteered to participate. We recorded the age of recruitment, biannual fitness test performance, and subsequent success in attaining a senior professional contract at the club across a period of 12 years. Only 53 (10%) of players were successful in obtaining a professional contract, with 68% of players who became professional being recruited at 12 years of age or older. Individuals recruited at an earlier age did not display a higher probability of success in attaining a professional contract. Bayesian regression models reported a consistent interaction between age and group for data on all performance measures. Moreover, "successful" academy graduates only physically outperformed their "unsuccessful" counterparts from age 13‐14 years onward, with either no differences in performance, or performance on physical fitness tests favoring "unsuccessful" players prior to this age. Findings suggest that high achievers during childhood and early adolescence may not develop into successful senior professionals, raising concerns about the predictive utility of talent identification models.